2011
DOI: 10.4103/0019-557x.89943
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use: A major risk factor for non communicable diseases in South-East Asia region

Abstract: Tobacco use is a serious public health problem in the South East Asia Region where use of both smoking and smokeless form of tobacco is widely prevalent. The region has almost one quarter of the global population and about one quarter of all smokers in the world. Smoking among men is high in the Region and women usually take to chewing tobacco. The prevalence across countries varies significantly with smoking among adult men ranges from 24.3% (India) to 63.1% (Indonesia) and among adult women from 0.4% (Sri La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 2 publications
1
53
1
Order By: Relevance
“…5 Our study showed hypercholesterolemia in 12.68%, hypertriglycerides in 25.35%, raised LDL in 2.82%, raised VLDL in 15.49% and low HDL in 22.82% which were much lower than the other studies done by Sharma et al, Alzeidan et al and Akintunde et al 1,5,7 The prevalence of cigarette smoking was in 8.45% among males and none of the women smoke which was similar to Sabale et al was (6.2%) and Ketkar et al and was much lower than Takur et al was (24.3%), Sharma et al was (12.8%) and Alzeidan et al was (12%). [5][6][7][8]11 The habit of alcohol consumption was seen in 7.04% which was lower than Sabale et al was (13.04%) as this study included all staff and higher than Sharma et al was (2.6%) as the study included only the habit of heavy drinking.…”
Section: Discussioncontrasting
confidence: 48%
“…5 Our study showed hypercholesterolemia in 12.68%, hypertriglycerides in 25.35%, raised LDL in 2.82%, raised VLDL in 15.49% and low HDL in 22.82% which were much lower than the other studies done by Sharma et al, Alzeidan et al and Akintunde et al 1,5,7 The prevalence of cigarette smoking was in 8.45% among males and none of the women smoke which was similar to Sabale et al was (6.2%) and Ketkar et al and was much lower than Takur et al was (24.3%), Sharma et al was (12.8%) and Alzeidan et al was (12%). [5][6][7][8]11 The habit of alcohol consumption was seen in 7.04% which was lower than Sabale et al was (13.04%) as this study included all staff and higher than Sharma et al was (2.6%) as the study included only the habit of heavy drinking.…”
Section: Discussioncontrasting
confidence: 48%
“…There are few studies which assess all the behavioural and biological risk factors in all the employees (teaching and non-teaching) working in Medical College. Thakur JS et al [11] got the prevalence across smoking among adult men in India as 24.3%. According to NFHS-III [12] the percentage of men and women in Maharashtra who drink alcohol is 24% and 0.4% respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Although smokeless tobacco (SLT) use is common among women, smoking among women is increasing [8],[9]. In Southeast Asia, tobacco is used in diverse forms, including cigarettes or bidis (dried tobacco rolled in paper or leaf), SLT such as chewing khaini (tobacco with slaked lime and aromatic spices), surti (dried tobacco leaves for chewing), or paan masala (tobacco with aromatic spices), sucking gutkha (mixture of tobacco and molasses available in small sachets), applying gul or gudaku as dentifrice, and inhaling nas and naswar (nasal inhalation of tobacco powder) [10].…”
Section: Introductionmentioning
confidence: 99%